Abdominal Organ Involvement in Blunt Injuries - Singh, Mousami; Kumar, Amit; Verma, Anoop Kumar; Kumar, Sanjeet; Singh , Abhas Kumar (Journal of Indian Academy of Forensic Medicine, 2012)
Visceral injuries of the abdomen following blunt trauma present a great medico-legal problem to  the forensic experts. Thus the doctor should remain alert to the development of signs and symptom after  blunt trauma to the abdomen in vehicular accident otherwise he may be charged of negligence. Among  55 fatal cases of blunt abdominal injury, maximum number of cases belongs to the age group 20-29 yrs.  Males were the predominant victims with ratio 4:1. It was found that road traffic accidents by heavy  vehicle like bus; car and truck were responsible for 70% of blunt abdominal injuries. Among 55 cases of  blunt injury, the incidence of the involvement of liver, spleen, small intestine, kidney, stomach and urinary  bladder were 67%, 30.91%, 18%, 10.9%, 9.09%, 5% cases respectively. Genitals were found injured in 3%  cases of blunt injury abdomen. For Blunt Injuries of Abdomen majority of the cases i.e. 78.18% were of  accidental, 18.18% were homicidal and 3.6% suicidal in nature. Immediate cause of death was shock and  hemorrhage and in those cases where death was delayed, cause of death was septicemia.
Keywords: Blunt Injuries; Vehicular Accident; Visceral Injuries